CONTINUOUS-WAVE MICROCHIP LASER GENERATION OF Tm:KLu(WO4)2 AND Tm:KY(WO4)2 CRYSTALS - O. P. Dernovich; S. V. Kurilchik; N. V. Gusakova; N. V. Kuleshov (Приборы и методы измерений, 2016)
Diode-pumped solid-state lasers are attractive for a variety of practical applications in many fields of human activity due to their high efficiency, compactness, and long durability. For applications in remote sensing lasers emitting in the spectral range of about 2 microns are required. Materials doped with trivalent thulium ions are promising active media emitting in this spectral range. Potassium rare-earth tungstates are attractive materials among Tm-doped crystals due to their suitable characteristics, such as high values of absorption and stimulated emission cross sections, incignificant concentration quenching of luminescence, well-proven technology of the high quality crystals growth. The purpose of this paper was to compare lasing properties of lasers based on potassium lutetium and potassium yttrium tungstate crystals doped with thulium ions in continuous-wave regime. Experiments were carried out with a diode pumping in microchip cavity configuration. The maximum power of laser radiation at 1947 nm of 1010 mW was obtained with Tm:KY(WO4)2 crystal with the slope efficiency with respect to the absorbed pump power of 51 %. When Tm:KLu(WO4)2 crystal was utilized an output power of 910 mW at 1968 nm wavelength with the slope efficiency of 38 % was obtained. With Tm:KLu(WO4)2 laser a tuning range over 160 nm range was realized with a prism inserted into the laser cavity.